2021
DOI: 10.1186/s12884-021-03618-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of ectopic pregnancy among pregnant women attending referral hospitals in southwestern part of Oromia regional state, Southwest Ethiopia: a multi-center case control study

Abstract: Background Ectopic pregnancy is an abnormal condition in which implantation of the blastocyst occurs outside the endometrium of the uterus. It is gynecological important, particularly in the developing world, because of associated with enormous rate of high morbidity, during the first trimester of pregnancy. A better understanding of its risk factors can help to prevent its prevalence. However, the determinants of ectopic pregnancy are not well understood and few researches conducted in our cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…The present study found that pelvic infection was observed in 24 women diagnosed with EP and had the following common symptoms: abdominal pain, vaginal bleeding, and Amenorrhea. This is similar to the study conducted in Ethiopia [ 7 , 18 , 19 ]. Prevention, or at least diagnosis and treatment, of pelvic infections would warrant primary care visits.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present study found that pelvic infection was observed in 24 women diagnosed with EP and had the following common symptoms: abdominal pain, vaginal bleeding, and Amenorrhea. This is similar to the study conducted in Ethiopia [ 7 , 18 , 19 ]. Prevention, or at least diagnosis and treatment, of pelvic infections would warrant primary care visits.…”
Section: Discussionsupporting
confidence: 91%
“…Journal of Pregnancy areas is far better than their rural counterparts, and this may influence the early presentation to EP care and treatment, which is supported by research in Ethiopia and India [8,18]. Consistent with other findings [1,22], women diagnosed with EP and anemia were also at higher risk of unfavorable EP outcome management.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…It is one of the top leading causes of maternal mortality in the first trimester and accounts for 10-15% of all maternal deaths. 9 Ectopic pregnancy is the leading cause of maternal morbidity and mortality worldwide. 9 Primary care physicians must maintain a high index of suspicion as clinical presentations vary widely from being asymptomatic to exhibiting hemodynamic compromise.…”
Section: Discussionmentioning
confidence: 99%
“…9 Ectopic pregnancy is the leading cause of maternal morbidity and mortality worldwide. 9 Primary care physicians must maintain a high index of suspicion as clinical presentations vary widely from being asymptomatic to exhibiting hemodynamic compromise. Commonly, the patient presents with abdominal pain, amenorrhea, and sometimes vaginal bleeding.…”
Section: Discussionmentioning
confidence: 99%